Content validity study: a gamification model to drive behavior change in defeating coronavirus disease 2019 pandemic - Nurul Hidayah Mat Zain; Siti Rahayu Abdul Aziz; Nor Aiza Moketar; Norshahidatul Hasana Ishak; Heny Hendrayati (Institute of Advanced Engineering and Science, 2022)
Gamification refers to transforming the environment to become more game-like to produce a positive experience. In this study, the researchers developed a gamification model, namely the GAMEBC model, to drive behavior change through a health awareness campaign in defeating the coronavirus disease 2019 (COVID-19) pandemic. The GAMEBC model was developed based on the self-determination theory (SDT) and gamification design literature. The GAMEBC model in this study involves four elements: competence, relatedness, autonomy, and engagement. Each element includes criteria that drive behavior change in health awareness campaigns. However, studies that validated the gamification model elements are limited, specifically to drive behavior change. Therefore, the content validity of the GAMEBC model instrument was carried out, and the analysis was based on thirteen expert reviews. The mean value and inter-rater agreement approach were implemented to examine the content validity ratio (CVR), item content validity index (I-CVI), and scale content validity index (S-CVI). The expert evaluation approach was implemented to review the GAMEBC model in terms of relevance and clarity. The data were analyzed using descriptive analysis. As a result of this work, we formulated an instrument that can be used to model and measure behavior change through the gamification approach in health awareness campaigns.